Insights on low cycle fatigue crack formation and propagation mechanism: A microstructurally-sensitive modeling. (July 2022) - Song, Kai; Wang, Kaimeng; Zhang, Libin; Zhao, Lei; Xu, Lianyong; Han, Yongdian; Hao, Kangda
Research highlights: A large-size 3D model was proposed to simulate fatigue crack formation at outer surface and propagation along slip plane. A micro-scale stored strain energy criterion was proposed for understanding the fatigue fracture mechanism. The complicated fatigue crack morphology and the change of growth rate from short crack to long crack could be simulated. The model provided an efficient simulation tool of the complex 3D fatigue crack formation and propagation. Abstract: A novel model for revealing low cycle fatigue (LCF) fracture mechanism was established based on molecular dynamics, extended finite element method, and representative volume element technology. Stored strain energy criterion provided the basic relationship for the proposed model. The proposed model was the 3D model for comprehensively simulating LCF crack formation at outer surface and propagation along slip system. In addition, micro-scale stored strain energy damage equations were proposed. The capability of the proposed model was confirmed by the microstructural fractography and 3D X-ray computed tomography. The complicated LCF crack growth direction and the secondary cracks accompanying the main crack could be simulated successfully. Particularly, the LCF crack length, the LCF crack formation/fracture life and morphology, the active slip system proportion, and the fracture angle were compared with experiment quantitatively and qualitatively. Two formation mechanisms of branch-shaped and main crack-independent secondary crack were determined. In addition, the microstructure had a strong influence on the LCF growth rate changing from short crack to long crack and the fluctuating crack growth rate during the short crack period. The proposed model had great potential to reveal the correlation between microstructure and LCF fracture mechanism. Graphical abstract: Image, graphical abstract